Prospects for the Mechanism of Spiroplasma Swimming - Sasajima, Yuya; Miyata, Makoto (Frontiers in Microbiology, 2021)
Spiroplasma are helical-shaped bacteria that lack a peptidoglycan layer. They are widespread globally as parasites of arthropods and plants. Their infectious processes and survival are most likely supported by their unique swimming system, which is unrelated to well-known bacterial motility systems such as flagella and pili. Spiroplasma swims by switching the right- and left-handed helical cell body alternately from the cell front. The kinks generated by the helicity shift travel down along the cell axis and rotate the cell body posterior to the kink position like a screw, pushing the water backward and propelling the cell body forward. An internal structure called the “ribbon” has been focused to elucidate the mechanisms for the cell helicity formation and swimming. The ribbon is composed of Spiroplasma-specific fibril protein and a bacterial actin, MreB. Here, we propose a model for helicity-switching swimming focusing on the ribbon, in which MreBs generate a force like a bi-metallic strip based on ATP energy and switch the handedness of helical fibril filaments. Cooperative changes of these filaments cause helicity to shift down the cell axis. Interestingly, unlike other motility systems, the fibril protein and Spiroplasma MreBs can be traced back to their ancestors. The fibril protein has evolved from methylthioadenosine/S-adenosylhomocysteine (MTA/SAH) nucleosidase, which is essential for growth, and MreBs, which function as a scaffold for peptidoglycan synthesis in walled bacteria.